Job Crafting Perawat Saat Pandemi Covid-19: Studi Perbadingan Pada 3 Jenis Kepemilikan Rumah Sakit Sulawesi Selatan - Andi Indahwaty AS; Irwandy Irwandy; Adhelia U Ady Mangilep; Indah Nur Insani; Ummu Kalsum (Jurnal Manajemen Kesehatan Indonesia, 2023)
ABSTRACT The COVID-19 pandemic has changed the structure and working methods of nurses to become more complex, dynamic and challenging. Nurses as the frontline are required to more quickly adapt to changes in the work environment. Proactive work behavior by giving assignments, relationships and work perceptions of nurses is the implementation of Job Crafting (JC). This study aims to compare how JC nurses are between 3 types of hospital ownership that provide Covid-19 services. This study involved 250 nurses in teaching hospitals, private hospitals and government hospitals in South Sulawesi, Indonesia. Data were analyzed using Compare Means and Linearity Test of Anova. The results showed that the highest scores were for Task Crafting (17.47), Cognitive Crafting (21.73) and Relational Crafting (18.44) in Government Hospitals. The lowest scores were for Task Crafting (17.16) at private hospitals, Cognitive Crafting (20.57) at teaching hospitals, and Relational Crafting (17.57) at private hospitals. Based on the results of the study it can be concluded that job crafting is more dominantly felt by nurses in government hospitals. In addition, of the three variables that have been tested, cognitive crafting has a stronger relationship effect than the other variables.  Keywords: Job crafting, Nurse, Pandemic, Hospital